A Simulation-Based Analysis of Dual-Counter Service Efficiency and Profitability - Laila, Sintya; Azizah, Nur; Prasetyo, M. Aditya; Hasibuan, Indah Larasati (Tsabit Journal of Computer Science, 2024)
Queue systems play a critical role in service industries, affecting customer satisfaction and operational performance. This study investigates the optimization of a dual-counter queue system consisting of regular and express counters, each with distinct service rates, operational costs, and profit margins. Using simulation modeling, the study aims to evaluate system performance, identify profit-maximizing strategies, and provide actionable insights for service management. The methodology involves simulating customer arrivals, service rates, and operational costs over a 60-minute period. Key metrics analyzed include the number of customers served, total operational costs, and net profit for each counter. The results reveal that express counters, despite higher operational costs, generate greater net profit per customer compared to regular counters. The findings underscore the importance of strategic resource allocation and cost-benefit analysis in queue management systems. This research contributes to the field by addressing a gap in the application of simulation for dual-counter systems, providing a framework for optimizing service operations across various industries. Further research is recommended to explore additional variables, such as customer preferences and dynamic arrival rates, to enhance the robustness of the simulation model. The purpose of the study entitled "A Simulation-Based Analysis of Dual-Counter Service Efficiency and Profitability" is most likely to analyze the effectiveness and efficiency of the service system in a dual-counter environment.